THE ROLE OF DA'I IN MODERN SOCIETY EMPOWERMENT - Ahmad Murjoko (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2022)
Research Objectives: To determine the role of da'i in empowering modern society. Research Methods: Qualitative. Research Results: So far the roles of da'i and da'iyah in society are identical as traveling preachers. Even though the role of a da'i will expand in line with the progress and expectations of society. It is possible for a preacher to be an economist at the same time, a preacher can also be a politician, or a preacher can also be a motivator, doctor to social worker and community empowerment expert. So the position and role of da'i and da'iyah become very important and strategic in society. Especially now that we are heading towards a modern society. This is because apart from being a proponent of Islamic teachings, he can also become a professional in other fields.